2015
DOI: 10.1002/cssc.201501460
|View full text |Cite
|
Sign up to set email alerts
|

A Step into an eco‐Compatible Future: Iron‐ and Cobalt‐catalyzed Borrowing Hydrogen Transformation

Abstract: Living on borrowed hydrogen: Recent developments in iron- and cobalt-catalyzed borrowing hydrogen have shown that economically reliable catalysts can be used in this type of waste-free reactions. By using well-defined inexpensive catalysts, known reactions can now be run efficiently without the necessary use of noble metals; however, in addition new types of reactivity can also be discovered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(28 citation statements)
references
References 36 publications
0
28
0
Order By: Relevance
“…As shown in Figure 1 To gain insight into the reaction pathway, additional experiments were performed (Scheme S3 (See Supplementary Materials)). A control experiment of acceptorless dehydrogenation of benzyl alcohol revealed that the combination of tBuOK and CoOx@NC-800 is essential for efficient benzaldehyde formation (See Supplementary Materials), which is generally considered the rate-determining step in the coupling of anilines with benzyl alcohols [17,18,57]. Of note is that the dehydrogenation reaction rate is considerably slower, mainly due to the lack of a hydrogen acceptor to drive the reaction equilibrium to the desired aldehyde.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Figure 1 To gain insight into the reaction pathway, additional experiments were performed (Scheme S3 (See Supplementary Materials)). A control experiment of acceptorless dehydrogenation of benzyl alcohol revealed that the combination of tBuOK and CoOx@NC-800 is essential for efficient benzaldehyde formation (See Supplementary Materials), which is generally considered the rate-determining step in the coupling of anilines with benzyl alcohols [17,18,57]. Of note is that the dehydrogenation reaction rate is considerably slower, mainly due to the lack of a hydrogen acceptor to drive the reaction equilibrium to the desired aldehyde.…”
Section: Resultsmentioning
confidence: 99%
“…The borrowing hydrogen strategy has been widely applied in organic transformations to construct various C-X (X = C, N, S) compounds in the last decade [17][18][19]. In this context, of particular importance is the N-alkylation of amines with alcohols to synthesize structurally complex primary and/or secondary amine compounds, which represents one of the most straightforward, efficient and eco-friendly methodologies for amine synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Following associative interactions conform this mechanism; the catalyst was found applicable in both transfer and pressure hydrogenation [20,25,26], Oppenauer oxidation [27], reductive amination [28], water-gas-shift-reactions [29], electro-reductions [30], alkylations [31], photocatalysis [32], and enantioselective dual catalysis typically for allylic alcohols [33][34][35][36][37][38] with formidable results. The capabilities of Knölker-type catalysts in asymmetric catalysis for normal ketones and imines have also been explored [39], however, their performance regarding enantioselectivity are generally found mediocre, as well for the corresponding ruthenium-based complexes (see Figure 1).…”
Section: Introductionmentioning
confidence: 98%
“…[1,2] Thea lcohol is dehydrogenated to ac arbonyl compound, followed by ar eaction with an ucleophile and subsequent reduction with the "borrowed" hydrogen. Due to dwindling crude oil reserves and growingp ublica wareness for the consequences of climate change, the search for alternative carbon resources is getting increasingly urgent.…”
mentioning
confidence: 99%
“…Products 3r and 3s were obtained in 46 and 49 %i solated yield. Considering that the incorporation of primary aliphatic alcohols was possible, we investigated the substrate scope ) 9CoCl 2 2…”
mentioning
confidence: 99%